The chemoprophylaxis of meningococcal disease in the Cape Town City Council area : an evaluation of programme efficacy - Girdler-Brown, Brendan Vaughan (Department of Public Health and Family Medicine, 2018)
This dissertation reports the findings of a study which was carried out in the Cape Town City Council area, in order to establish whether the offering of rifampicin to household contacts, of patients with meningococcal disease, resulted in protection of those contacts against developing the disease during a 32 week follow up period. The study took the form of a retrospective follow up of 3 350 household contacts of 412 cases notified over a 4-year period (mid 1988-mid 1992). It was found that the offering of rifampicin to the household contacts resulted in an odds ratio of not developing meningococcal disease over the 32-week follow up period of 14, 17 (SD = 12, 34). Although there was a tendency for contacts who were not offered rifampicin to have been younger, and of male gender, when compared to those who were offered prophylaxis, these demographic differences were not statistically significant at the 0,05 level. Furthermore, three out of the four male second cases, all in the younger age group, were in fact offered prophylaxis. It seems desirable that prophylaxis should be given as soon as possible. It is concluded, therefore, that the offering of rifampicin to household contacts of patients with meningococcal disease, living under the prevailing social circumstances in the Western Cape, has protective benefit for those contacts. It is likely that the chemoprophylaxis programme prevented up to 88 cases of meningococcal disease over the study period of four years, as well as preventing 8 deaths from this disease, in the CCC population.